Determinantes de las exportaciones de las empresas agroindustriales peruanas 2002-2019; Determinants of the exports of peruvian agroindustrial companies 2002-2019 - Darwin Alejandro Siancas Escobar; María-Verónica Seminario-Morales; Lucy Mariella García Vilela; Yersi-Luis Huamán Romaní (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2024)
– This is a research on Political Economy, Macroeconomics and Applied Economy, based on the Austrian Economics' approach over the economic cycles and applied to the Spanish case (2002-2014). Attention is focused on the endemic problem of economic cycles, such as successive and distorting periods of boom and recession that modern economies suffer, such as the Spanish economy. This is an inquire to find empirical evidence in favor of the Austrian Business Cycle Theory, for the specific Spanish case between 2002 and 2014, through the application of econometric methods. Consequently, after reviewing the scarce previous econometric literature on the Austrian cycle, this research has as its main objective to explain and illustrate the boom with the effective introduction of the euro in 2002, the recession during 2008-11 and the recovery in 2014, using the Austrian theory of the endogenous and non-neutral monetary cycle.
Keywords: C23; F14; Q17; 330; Panel data; exports; agribusiness